Deformation behavior of slab warping for longitudinal continuous rigid slab under temperature effect. Issue 13 (October 2019) - Chen, Zui; Xiao, Jieling; Liu, Xueyi; Qin, Hongpei; Yang, Rongshan
Longitudinally coupled prefabricated slab track is prone to slab warping under the non-uniform temperature field. Analytical expressions for the displacement field of the track slab during the warping process are developed hereby based on equilibrium differential equations, and the expressions are verified through a numerical model by finite element method in ANSYS package. Through analyzing the factors such as types of temperature distribution, slab gravity, and rail weight, regulations of warping deformation for the track slab are systematically analyzed. Research shows that the displacements in the x and z directions are linearly related to the respective components during the warping deformation. The displacement in y direction has a quadratic relationship with x and z components. Temperature gradient is the pivotal factor to lead the warping of the track slab, and the type of temperature distribution has less effect on the warping displacement. If track slab remains unwarped under the effect of slab gravity, temperature gradient should be maintained in the range of –18°C/m–13°C/m. Rail weight has less influence on slab warping.